Metode Sig Dalam Potensi Wilayah Bencana Banjir Bandang Di Kecamatan Ile Ape - Hendrikus Hewar; Marinus I.J.Lamabelawa (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2025)
Ile Ape Regency is one of the areas in Lembata Regency that geographically has a high level of vulnerability to natural disasters, especially flash floods. This condition is reinforced by the high intensity of rainfall and the complex topography of the area which are the main triggers for flash floods in the area. This study aims to map areas of potential flash flood disaster in Ile Ape Regency using the overlay method based on Geographic Information Systems (GIS). The overlay method allows the combination of various layers of spatial data such as slope gradient, soil type, land use, and rainfall to produce a more accurate and detailed flash flood vulnerability zoning map. The results of this study are expected to provide a comprehensive picture of the level of vulnerability of the area to flash flood disasters, as well as become a strategic reference for local governments and related parties in preparing mitigation measures, spatial planning, and disaster management in a targeted and sustainable manner in Ile Ape Regency.